2010
DOI: 10.1016/j.ijsolstr.2009.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Unloading of an elastic–plastic spherical contact under stick contact condition

Abstract: a b s t r a c tThe unloading process of an elastic-plastic spherical contact under stick contact condition is analyzed for various material properties. The evolution of normal and shear stress distribution at the contact area as well as the residual profile of the sphere and residual von Mises stresses inside the sphere are presented. Empirical expressions for the residual interference and for the evolution of the interference and contact area during the unloading are provided. Good agreement with experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 26 publications
3
15
0
Order By: Relevance
“…However, for a given contact approach, the contact area on unloading is greater than on loading during most of the unloading phase of the loading/separation calculation (equivalently, the difference in area between loading and unloading in the contact area vs. contact approach plot is positive). This observation is consistent with the experimental investigation of Ovcharenko,et al (37) and the theoretical work of Zait, et al (38) without adhesion. By comparing Figs.…”
Section: Resultssupporting
confidence: 93%
“…However, for a given contact approach, the contact area on unloading is greater than on loading during most of the unloading phase of the loading/separation calculation (equivalently, the difference in area between loading and unloading in the contact area vs. contact approach plot is positive). This observation is consistent with the experimental investigation of Ovcharenko,et al (37) and the theoretical work of Zait, et al (38) without adhesion. By comparing Figs.…”
Section: Resultssupporting
confidence: 93%
“…The contact area and the mean contact pressure showed good correlation with the experimental results given by Ovcharenko et al [35]. Zait et al [36] studied the unloading process of a spherical contact under full stick condition, and proposed the residual profile of the sphere and residual von Mises stresses within the sphere. The theoretical results accorded well with the experiments.…”
Section: Introductionsupporting
confidence: 75%
“…However, substantial differences were found for the contact area and residual tip curvature under slip and stick contact conditions. Very good correlation was found between the theoretical results of Brizmer et al (2006b) and Zait et al (2010), and the experiments of Ovcharenko et al (2006) that were performed with relatively smooth surfaces (Ra < 100 nm) in dry environment. Based on these results, it is reasonable to suggest that in many practical applications stick contact condition may be more valid than slip condition.…”
Section: Introductionsupporting
confidence: 58%
“…However, the evolution of the plastic zone with increasing interference was substantially different for contacts under perfect slip or under full stick contact conditions. Zait et al (2010) studied unloading of elastic-plastic spherical contact under stick contact condition in comparison with the unloading under slip by Etsion et al (2005). They found that the two different contact conditions had negligible effect on the contact interference.…”
Section: Introductionmentioning
confidence: 99%